The Value of Shear Wave Elastography in the Diagnosis of Breast Cancer Axillary Lymph Node Metastasis and Its Correlation With Molecular Classification of Breast Masses - Luo, Changyun; Lu, Li; Zhang, Weifu; Li, Xiangqi; Zhou, Ping; Ran, Zhangshen (Frontiers in Oncology, 2022)
Objective: To explore the diagnostic value of shear wave elastography examination (SWE) on the axillary node metastasis (ANM) in breast cancer, this study aimed to explore the correlation between the SWE features and different molecular types of breast cancer, and to check the elastic modulus differences among the molecular types. Methods: The breast cancer patients from November 2020 to December 2021 were subjected to both of the conventional ultrasonic examination (CUE) and the SWE before ultrasound-guided ALN biopsy or the axillary lymph node dissection (ALND). Using the pathological results as the gold standard to draw the receiver operating characteristic (ROC) curve. Results: The SWE outperforms the CUE, but their conjunctive use performs best. No significant correlation was found between the elastic modulus values and the molecular types of breast cancer. Conclusion: The SWE can be used as a routine auxiliary method of the CUE for the ALN metastasis.